A modified composite nonwoven fabric material and preparation process

By using organosilicon compounds with specific structures as modifiers and optimizing process parameters, the problems of single performance and low production efficiency of traditional nonwovens are solved, and high-performance, multifunctional, green and environmentally friendly modified composite nonwoven materials are prepared.

CN119189455BActive Publication Date: 2025-04-29SHANGHAI RE-POLY ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411730530.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-29
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The performance and functions of traditional nonwoven fabrics are relatively single, which is difficult to meet the increasingly diversified application needs. In addition, there are problems such as large resource consumption, low production efficiency, complex process, and high energy consumption during the production process.

Method used

The silicone compound with a specific structure is used as a modifier, and the nonwoven fabric is given excellent hydrophilicity, hygroscopicity and corrosion resistance through simple immersion and drying processes. By optimizing process parameters such as hydrospuncture, drying, and shaping, production efficiency is improved and energy consumption is reduced.

Benefits of technology

A composite nonwoven fabric material with spunbond nonwoven fabric strength and staple fiber nonwoven fabric softness was prepared, which broadened the application field of nonwoven fabrics, and the process was environmentally friendly and efficient, in line with the concept of green manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119189455B_ABST
    Figure CN119189455B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified composite nonwoven fabric material and a preparation process, belonging to the technical field of nonwoven fabrics. The process uses recycled polyester as a raw material, prepares a high-strength recycled polyester spunbond nonwoven fabric by direct polymer web-forming, and overlaps the recycled polyester short fiber dry-combing fiber web, then entangles and composites it by water spunlace, and finally treats it with a modifier containing a specific organic matter to obtain a composite nonwoven fabric material having both the strength of the spunbond nonwoven fabric and the softness of the short fiber nonwoven fabric; wherein the modifier is prepared by mixing organic matter of formula I and formula II in a certain proportion, and generating an organic matter of formula IV through a multi-step reaction; the organic matter contains a polar group, which can be combined with nonwoven fibers through hydrogen bonds and the like to improve the comprehensive performance of the material; the prepared modified composite nonwoven fabric material has excellent comprehensive performance and has broad application prospects in many fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonwoven fabrics, and in particular relates to a modified composite nonwoven fabric material and a preparation process. Background Art

[0002] Nonwoven fabric, also known as non-woven fabric, is a fabric that does not require spinning and weaving. It is mainly made by directional or random arrangement of textile staple fibers or filaments to form a fiber mesh structure, and then reinforced by mechanical, thermal bonding or chemical methods. Nonwoven fabrics break through the traditional textile principles and have the characteristics of short process flow, fast production rate, high output, low cost, wide application, and multiple sources of raw materials. In terms of product characteristics, nonwoven fabrics have good characteristics such as light weight, softness, breathability, and environmental protection, and different types of nonwoven fabrics also have specific functional attributes.

[0003] Nonwoven fabrics are widely used in medical and health care, personal care, industrial wiping, agriculture, construction and other fields. In recent years, with the enhancement of environmental awareness and the advancement of technology, the application of nonwoven fabrics in green and environmentally friendly products has received more and more attention. However, in the traditional nonwoven fabric production, especially the wet web forming technology, there are problems such as large water consumption and low production efficiency. In addition, many nonwoven fabric products rely on virgin materials, which consumes a lot of resources and does not meet the requirements of sustainable development.

[0004] In order to overcome the shortcomings of traditional nonwoven fabrics, researchers have begun to explore various modification methods to improve the performance and environmental friendliness of nonwoven fabrics. For example, inorganic powders such as calcium carbonate are used to modify polypropylene spunbond nonwoven fabrics, aiming to improve the comprehensive performance of the material through filling modification while reducing costs and environmental impact. This modified nonwoven fabric is not only widely used in environmentally friendly shopping bags and other fields, but also has good degradability and sustainability.

[0005] The specific innovation directions of modified composite nonwovens are as follows:

[0006] Material selection and composite technology: Recycled polyester fiber and recycled PET bottle flakes are composited through dry spunlace process to form a nonwoven fabric material with a specific structure. The staple fiber layer of this material is a disordered entangled structure, and the spunbond nonwoven fabric layer is a mesh structure with piercing points, which gives the material a soft feel and good performance.

[0007] Environmental protection and sustainability: The dry web-forming process is used to replace the traditional wet web-forming process, which not only reduces water consumption but also improves the softness of the material. By strictly controlling the temperature and filtering conditions of the wire drawing process, the quality of the recycled material is ensured to be stable, thereby improving the performance stability of the product.

[0008] Versatility and high performance: By combining the advantages of different fibers, through reasonable process design and material combination, high-performance nonwoven fabric materials with multifunctionality are prepared. For example, ultrafine fiber spunbond spunlace nonwoven fabrics have good moisture absorption and air permeability, and are widely used in artificial leather base fabrics, high-grade wiping cloths, filter materials and other fields.

[0009] As the world pays more attention to environmental protection and sustainable development, the research and application of modified composite nonwoven materials will continue to deepen. Future research directions include:

[0010] Development of new materials: Explore the application of more renewable and degradable materials in nonwovens to further reduce the impact on the environment.

[0011] Innovation in process technology: Improve production efficiency and product performance while reducing production costs and promoting the green development of the nonwovens industry.

[0012] Expansion of application areas: Develop more nonwoven products with specific functions in the fields of medical care, agriculture, construction, etc. to meet the needs of different markets.

[0013] In summary, the research on modified composite nonwoven fabric materials and their preparation technology will not only help to improve the comprehensive performance of nonwoven fabrics, but also promote the sustainable development of the industry. It has broad application prospects and important social value. Summary of the invention

[0014] 1. Problems to be solved

[0015] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a modified composite nonwoven fabric material and a preparation process, specifically to solve the following problems: the performance and function of traditional nonwoven fabrics are relatively single, and it is difficult to meet the increasingly diverse application needs. The present invention prepares a composite nonwoven fabric material that has both the strength of spunbond nonwoven fabrics and the softness of short fiber nonwoven fabrics through a reasonable production process and material combination, thereby broadening the application field of nonwoven fabrics.

[0016] Conventional nonwoven fabric modification methods have problems such as complex process, high cost, environmental pollution, etc. The present invention uses an organosilicon compound with a specific structure as a modifier, and through a simple soaking and drying process, imparts excellent hydrophilicity, hygroscopicity and corrosion resistance to the nonwoven fabric, and the modification process is green and environmentally friendly.

[0017] The existing nonwoven fabric finishing process has high energy consumption, low production efficiency and unstable product quality. The present invention optimizes the process parameters such as spunlace, drying and shaping, improves production efficiency and reduces energy consumption while ensuring the modification effect, and adopts surface contact ironing shaping to form a smooth and flat effect on the material surface, thereby improving the appearance quality of the fabric.

[0018] In summary, the present invention aims to solve the problems existing in the production and modification process of traditional non-woven fabrics, such as large resource consumption, low production efficiency, single performance, complex process, high energy consumption, etc., and develop a high-performance, multi-functional, green and environmentally friendly modified composite non-woven fabric material and preparation process to meet the growing market demand for functional non-woven materials and promote the sustainable development of the industry.

[0019] 2. Technical solution

[0020] To solve the above problems, the technical solution provided by the present invention is:

[0021] A preparation process of a modified composite nonwoven fabric material comprises the following steps:

[0022] (1) The recycled polyester is melt-treated and spun to obtain a recycled polyester spunbond nonwoven fabric with a gram weight of 50-60 g / m 2 ;

[0023] (2) opening and combing the regenerated polyester staple fibers to obtain a regenerated polyester staple fiber web;

[0024] (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) in a mass ratio of (2-5):(1-4) to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer;

[0025] (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric;

[0026] (5) soaking the spunlace composite nonwoven fabric obtained in step (4) in a modifier, then performing hot air penetration drying and shaping, and finally winding, slitting and packaging;

[0027] In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:(15-30);

[0028] The preparation method of the modifier is as follows:

[0029] An organic substance of formula I and an organic substance of formula II are stirred and mixed in a mass ratio of 1:(1.5-2) to obtain a mixture, dimethyl sulfoxide (5-8 times the mass of the mixture) and dicyclohexylcarbodiimide (0.1-0.2 times the mass of the mixture) are added, and the mixture is heated at 60-75° C. for reaction for 4-8 hours to obtain an organic substance of formula III, and then the organic substance of formula III is reacted by the following reaction: 1.1-1.5 times the mass of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is added to the organic substance of formula III, and stirred at room temperature for 30 minutes, 28wt% ammonia solution (3-5 times the mass of the organic substance of formula III) is added, and stirred at room temperature for 2-4 hours, 2-3 times the mass of ether is added, and vacuum drying is performed to obtain a white or off-white powder organic substance of formula IV;

[0030] The structure of Formula I is as follows:

[0031] (I),

[0032] The structure of Formula II is as follows:

[0033] (II), wherein the preparation method of the organic compound of formula II is as follows: 1 molar equivalent of guanidine thiourea is dissolved in 10 molar equivalents of 1 mol / L NaOH solution, cooled to 0°C in an ice bath, 1.1 molar equivalents of methyl cyanoacetate are slowly added dropwise, the temperature is controlled to be below 10°C, and the temperature is naturally raised to room temperature after the addition is completed, and the reaction is continued by stirring for 4 hours. After the reaction is completed, the pH is adjusted to 6 with dilute hydrochloric acid, and suction filtration is performed to obtain a white solid 2-amino-4-hydroxypyrimidine, then 1 molar equivalent of 2-amino-4-hydroxypyrimidine is dissolved in 10 molar equivalents of anhydrous methanol, 1.5 molar equivalents of anhydrous potassium carbonate are added, stirred, heated to reflux at 75°C, 1.2 molar equivalents of methyl iodide are slowly added dropwise, and the mixture is refluxed. The mixture was reacted for 4 hours, dissolved in dichloromethane, washed with water, and dried to obtain 2-amino-4-methoxypyrimidine. Then, 1 molar equivalent of 2-amino-4-methoxypyrimidine and 1.2 molar equivalents of ethyl acetoacetate were dissolved in 10 molar equivalents of anhydrous ethanol, heated under reflux at 80°C for 8 hours to obtain a pyrazolo[1,5-a]pyrimidine compound. 1 molar equivalent of the pyrazolo[1,5-a]pyrimidine skeleton compound was dissolved in 10 molar equivalents of N,N-dimethylformamide, cooled in an ice bath, and 1.2 molar equivalents of 60% by mass were slowly added. Sodium hydride, stirred for 20 minutes, slowly added 1.2 molar equivalents of N-(2-bromoethyl) anthranilic acid, naturally warmed to room temperature, continued to stir and react for 3 hours, dried to obtain an N-alkylated product, and finally, dissolved 1 molar equivalent of the N-alkylated product in 10 molar equivalents of anhydrous dichloromethane under ice bath cooling, slowly added 1.5 molar equivalents of chlorosulfonic acid, controlled the temperature below 5°C, naturally warmed to room temperature after the addition was completed, continued to stir and react for 4 hours, slowly poured the reaction solution into ice water, adjusted the pH to neutral, and dried to obtain;

[0034] The structure of Formula III is as follows:

[0035] (III),

[0036] The structure of Formula IV is as follows:

[0037] (IV).

[0038] The process parameters for winding, slitting and packaging are as follows:

[0039] Winding parameters:

[0040] Use special winding equipment for winding.

[0041] The winding tension is controlled at 30-100N / m;

[0042] Slitting parameters:

[0043] Use a special slitting machine for slitting.

[0044] The slitting speed is controlled at about 200m / min.

[0045] The cutter uses multiple sets of circular knives, about 21 sets in number.

[0046] Slitting capacity covers 35-600g / m 2 Spunlace fabric,

[0047] The maximum width of base paper is 1700mm and the maximum diameter is 1200mm;

[0048] Paper edge correction control:

[0049] Tension control, matching with winding tension;

[0050] Packaging parameters:

[0051] Use fully automatic packaging machines to save labor.

[0052] Before packaging, the finished products are inspected online to remove unqualified products.

[0053] The packaging quantity and size can be set flexibly.

[0054] The packaging material should be moisture-proof and dust-proof plastic film.

[0055] When selecting equipment, you can refer to the above process parameters and choose the appropriate winding machine, slitting machine and packaging machine. Through reasonable tension control, speed matching and process detection, high-quality finished spunlace fabric rolls can be obtained. The automation and intelligence of the packaging process can improve production efficiency and reduce labor costs.

[0056] This process uses recycled polyester fiber as raw material, prepares high-strength recycled polyester spunbond nonwoven fabric through direct polymer web-forming, and then overlaps it with recycled polyester staple fiber dry-combed fiber web, and then hydroentangles it, and finally treats it with a modifier to obtain a composite nonwoven fabric material that has both the strength of spunbond nonwoven fabric and the softness of staple fiber nonwoven fabric. This dry composite process can effectively reduce water resource consumption and is in line with the concept of sustainable development.

[0057] Preferably, the parameters of the recycled polyester in step (1) are as follows:

[0058] Melting point: (250-265) ± 2°C, intrinsic viscosity: (0.65-0.75) ± 0.025 dl / g;

[0059] In step (1), the recycled polyester is subjected to the following treatment before being melt-treated:

[0060] The recycled polyester is melted at the melting point, and then crystallized, wherein the crystallization temperature is 140-150°C, and the crystallization time is 20-30 minutes. Finally, it is dried, wherein the drying temperature is 150-160°C, and the drying time is 8-10 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

[0061] Melting equipment: The recycled polyester can be melted in a heated stirring tank, and the temperature is controlled at the melting point of the recycled polyester, i.e. 250-265℃±2℃. Stirring can prevent local overheating and degradation of the melt.

[0062] Crystallization equipment: The melted recycled polyester needs to be crystallized at 140-150℃ for 20-30min. A heat preservation tank with stirring or a crystallization dryer can be used. Stirring can prevent the polyester particles from sticking together. Crystallization can improve the crystallinity and thermal stability of polyester.

[0063] In addition to the above equipment, corresponding conveying equipment is also required to transfer materials between different equipment. The entire pretreatment process should be carried out in a closed or isolated clean room to avoid moisture absorption again. The pretreated recycled polyester should be sealed and packaged in time or sent to the next melt extrusion process.

[0064] Preferably, the parameters of the melt treatment in step (1) are as follows:

[0065] A twin-screw extruder is used for melt extrusion, wherein the feed section temperature is 265°C, wherein the melting section temperature is 270-280°C, wherein the mixing section temperature is 280-285°C, wherein the discharge section temperature is 285-290°C;

[0066] The parameters of the spinning process in step (1) are as follows:

[0067] The temperature of the spinning box is controlled at 280-300°C, the air pressure of the airflow drafting device of the spinning box is controlled at 5-8 bar, the spinning speed of the spinning box is 800-1500 m / min, and the spinneret aperture of the spinning box is 0.2-0.4 mm.

[0068] The zoned temperature control of the twin-screw extruder can achieve gradual melting, mixing and homogenization of polyester. The temperature of the feeding section is slightly lower than the melting point of polyester to prevent polyester from sticking during feeding; the temperature of the melting section is higher than the melting point of polyester to fully melt the polyester; the temperature of the mixing section is higher to promote uniform mixing of the melt; the temperature of the discharge section is the highest to reduce the melt viscosity and facilitate extrusion molding.

[0069] The temperature of the spinning box should be higher than the melting point of polyester to maintain good fluidity of the polyester melt during the spinning process. Air drafting can stretch the fiber, reduce the fiber diameter and increase the fiber strength. The spinneret aperture determines the initial fiber diameter. The spinning speed affects the stretching ratio and cooling rate during the fiber forming process, which in turn affects the final shape and performance of the fiber.

[0070] By rationally controlling the melt extrusion and spinning process parameters, recycled polyester spunbond nonwoven fabrics with excellent performance can be obtained, laying the foundation for subsequent compounding and modification.

[0071] Spinning equipment manufacturers and equipment types:

[0072] Dalian Huayang New Materials Technology Co., Ltd. specializes in the research and development and industrial promotion of new processes, new products, and complete sets of technologies and equipment for spunbonded nonwoven materials such as polyester and other high-molecular polymers, and provides customized overall equipment solutions.

[0073] Preferably, the regenerated polyester staple fiber described in step (2) has a fineness of 1.3-1.7 dtex, a length of 38-51 mm, and contains (0.3±0.02)% by mass of titanium dioxide matting agent.

[0074] Preferably, the method for opening in step (2) is as follows:

[0075] The feeding speed is 0.5-2m / min, the cylinder speed is 600-1500rpm, the gap between the cylinder and the working roll is 0.1-1mm, and the air flow rate is 1-10m / s;

[0076] The method of combing in step (2) is as follows:

[0077] The density of the card clothing is 120-200 needles / inch, the production speed is 50-80m / min, and the drafting multiple is 1.2-1.5 times.

[0078] Preferably, the parameters for unwinding in step (3) are as follows:

[0079] The unwinding tension is 0.5-2N / cm and the unwinding speed is 50-80m / min.

[0080] For equipment selection:

[0081] Opening machine: Domestic manufacturers include Zhengzhou Textile Machinery, Changshu Feilong, Laroche, Trützschler, and autufa.

[0082] Features: Each machine is custom designed to meet the specific manufacturing needs of the production process. Continuous protection, easy to operate and maintain.

[0083] In summary, when choosing an opener and unwinder, you need to choose the appropriate manufacturer and model based on the specific raw material properties, production requirements, etc. It is recommended to contact the manufacturer, provide raw material samples and process parameters, and obtain targeted equipment selection suggestions. At the same time, consider factors such as equipment capacity, degree of automation, energy consumption, etc., and balance production efficiency and cost.

[0084] Preferably, the parameters of the hydroentanglement reinforcement in step (4) are as follows:

[0085] The number of hydroentanglement reinforcement passes is six;

[0086] For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle;

[0087] For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement;

[0088] As for the water needle pressure, the water needle pressure is controlled at 50-70bar during the first hydroentanglement reinforcement, 100-120bar during the second and third hydroentanglement reinforcement, 170-180bar during the fourth hydroentanglement reinforcement, 100-120bar during the fifth hydroentanglement reinforcement, and 90-110bar during the sixth hydroentanglement reinforcement.

[0089] The following equipment and manufacturers are used in the hydroentanglement reinforcement process:

[0090] ANDRITZ Perfojet:

[0091] Manufacturer: Suzhou Jiuyi High-Tech Nonwoven Equipment Co., Ltd.

[0092] Model: TUE-TC-100(8);

[0093] Features:

[0094] Working width 3600mm;

[0095] Contains one pre-wetting jet and seven detangling jets.

[0096] The water jet head can produce high-powered continuous and consistent water jets throughout the entire working pressure.

[0097] Each water jet head is connected to the frame through guide pillars and can be precisely positioned.

[0098] Jet strips:

[0099] Manufacturers: Groz-Beckert, Eeka,

[0100] Model: HyTec water jet strip;

[0101] Features:

[0102] Jet strips are available in all common sizes, designs and nozzle geometries.

[0103] The product range includes jet strips in all common widths and thicknesses with a total length of up to 6200 mm.

[0104] There are usually single, double or triple row nozzle arrangements;

[0105] Water jet head:

[0106] Manufacturer: Andritz,

[0107] Model: neXjet water jet;

[0108] Features:

[0109] Top-notch design ensures the best quality water needles.

[0110] Water is distributed through a patented, continuous flume.

[0111] Optimize efficiency using the latest computer-based fluid dynamics modeling tools,

[0112] Equipped with an automatic cleaning system to avoid pulp accumulation.

[0113] The selection and parameter control of the above equipment directly affect the quality of spunlace nonwovens. It is recommended to contact the manufacturer, provide process parameters, and obtain targeted equipment selection suggestions. At the same time, consider factors such as equipment capacity, degree of automation, energy consumption, etc., and balance production efficiency and cost.

[0114] Preferably, the shaping method in step (5) is surface contact ironing shaping, and its parameters are as follows:

[0115] The temperature is 160-220℃, the time is 1-3s, the pressure is 10-30N / mm, and the tension is 30-100N / m.

[0116] Ironing machine / calender:

[0117] Manufacturer: Andritz,

[0118] model:

[0119] teXcal Raconip L calender,

[0120] Line pressure: up to 300N / mm,

[0121] Roller width: up to 3600mm,

[0122] Features: Clothing and home textile experts;

[0123] teXcal s-roll calender:

[0124] Line pressure: up to 400N / mm,

[0125] Roller width: up to 3600mm,

[0126] Features: All-round textile calender.

[0127] Forming machine:

[0128] Manufacturer: Mayer,

[0129] Hot air setting machine POWER-HEAT,

[0130] Working width: 1.8-3.4m,

[0131] Heating temperature: up to 250°C,

[0132] Production speed: up to 40m / min,

[0133] Features: Hot air circulation system, uniform heating effect on the fabric surface.

[0134] Cylinder type steam setting machine POWER-STEAM:

[0135] Working width: 1.8-3.4m,

[0136] Steam pressure: up to 10 bar,

[0137] Production speed: up to 80m / min,

[0138] Features: Saturated steam heating, soft and plump feel.

[0139] The above equipment can achieve the high temperature rapid shaping described in the patent at a temperature of 160-220°C and a time of 1-3s. At the same time, the calender can provide the required line pressure of 10-30N / mm, and the shaping machine can control the cloth tension at 30-100N / m through devices such as tension rollers.

[0140] In addition, regarding the sample process, the water jet pressure parameters are:

[0141] HP1: 70 bar;

[0142] HP2: 105 bar (reverse stab);

[0143] HP3: 100 bar;

[0144] HP4: 170 bar;

[0145] HP5: 120 bar;

[0146] HP6: 110 bar.

[0147] Process parameters:

[0148] Winding speed: 35 m / min;

[0149] Product weight: 90 g / m² (60 g / m² PET spunbond + 30 g / m² PET staple fiber web);

[0150] Drying temperature: 135 ℃;

[0151] Ironing and shaping temperature: 170 ℃;

[0152] Ironing roller pressure: 2 Kg.

[0153] A modified composite nonwoven fabric material is prepared by the above-mentioned preparation process of the modified composite nonwoven fabric material.

[0154] 3. Beneficial effects

[0155] The modifier molecules contain polar groups such as sulfonic acid group (-SO3H), carboxyl group (-COOH), secondary amine group (-NH-), etc., which can be combined with the surface of non-woven fibers through hydrogen bonds, electrostatic effects, etc., to increase the adsorption amount and bonding strength of the modifier on the fiber surface. These groups can also give the material excellent hydrophilicity and hygroscopicity. Nitrogen-containing heterocyclic rings such as pyrimidine rings and pyrazole rings in the modifier molecules can enhance the interaction force between the modifier molecules through π-π stacking and other effects, which is conducive to the formation of a uniform and dense modified layer on the fiber surface. This tightly arranged modified layer can improve the corrosion resistance and anti-aging properties of the material. Flexible alkyl segments such as ethyl in the modifier molecules can increase the flexibility of the molecules and form entanglements with the fibers, thereby improving the softness of the modified non-woven fabric and the drape of the fabric. The present invention adopts a spunlace composite process to composite the modifier with staple non-woven fabrics and spunbond non-woven fabrics, combining the advantages of the two non-woven fabrics to obtain a composite material with both the strength of spunbond fabrics and the softness of staple fiber fabrics. The spunlace process is environmentally friendly and in line with the concept of green manufacturing.

[0156] The present invention optimizes the process parameters such as spunlacing, drying and shaping, thereby improving production efficiency and reducing energy consumption while ensuring the modification effect. The surface contact ironing shaping is adopted to form a smooth and flat effect on the surface of the material, thereby improving the appearance quality of the fabric.

[0157] In summary, the present invention uses a modifier to modify the spunlace composite non-woven fabric, and the obtained modified composite non-woven fabric material has excellent hydrophilicity, hygroscopicity, corrosion resistance and softness, and the production process is environmentally friendly and efficient, which provides a new idea for the development of functional non-woven materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0158] Figure 1 is a micrograph of a modified composite nonwoven fabric material prepared in Embodiment 3 of the present invention;

[0159] Figure 2 is a hydrogen spectrum of the modifier according to Embodiment 3 of the present invention;

[0160] Figure 3 is a carbon spectrum of the modifier of embodiment 3 of the present invention;

[0161] Figure 4 is a hydrogen spectrum of the organic compound of formula II according to embodiment 3 of the present invention;

[0162] Figure 5 is a carbon spectrum of the organic compound of formula II according to embodiment 3 of the present invention;

[0163] Figure 6 is a hydrogen spectrum of the organic compound of formula III according to embodiment 3 of the present invention;

[0164] Figure 7It is the carbon spectrum of the organic substance of formula III according to implementation scheme 3 of the present invention. DETAILED DESCRIPTION

[0165] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0166] It should be noted that, in the present invention, all weight parts or other mass ratios involved are based on the international standard unit kilogram (Kg).

[0167] Implementation 1

[0168] The preparation process of the modified composite nonwoven fabric material comprises the following steps:

[0169] (1) The recycled polyester is melt-treated and spun to obtain a recycled polyester spunbond nonwoven fabric having a gram weight of 50 g / m 2 ;

[0170] The parameters of the recycled polyester in step (1) are as follows:

[0171] Melting point: 250°C, intrinsic viscosity: 0.75dl / g;

[0172] In step (1), the recycled polyester is subjected to the following treatment before being melt-treated:

[0173] The recycled polyester is melted at the melting point, and then crystallized, wherein the crystallization temperature is 140°C, and the crystallization time is 30 minutes. Finally, it is dried, wherein the drying temperature is 150°C, and the drying time is 10 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

[0174] The parameters of the melt treatment in step (1) are as follows:

[0175] The melt extrusion was performed using a twin-screw extruder, wherein the feed section temperature was 265°C, wherein the melting section temperature was 270°C, wherein the mixing section temperature was 285°C, wherein the discharge section temperature was 285°C;

[0176] The parameters of the spinning process in step (1) are as follows:

[0177] The temperature of the spinning manifold is controlled at 280° C., the air pressure of the airflow drafting device of the spinning manifold is controlled at 8 bar, the spinning speed of the spinning manifold is 800 m / min, and the aperture of the spinneret of the spinning manifold is 0.4 mm.

[0178] (2) The regenerated polyester staple fibers are opened and combed to obtain a regenerated polyester staple fiber web having a density of 90 g / m 2 ;

[0179] The regenerated polyester staple fiber described in step (2) has a fineness of 1.3 dtex, a length of 51 mm, and contains 0.3% by mass of titanium dioxide matting agent.

[0180] The method of loosening in step (2) is as follows:

[0181] The feeding speed is 0.5m / min, the cylinder speed is 1500rpm, the gap between the cylinder and the working roll is 0.1mm, and the air flow rate is 10m / s;

[0182] The method of combing in step (2) is as follows:

[0183] The card clothing density is 120 needles / inch, the production speed is 80m / min, and the draft ratio is 1.2 times.

[0184] (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) in a mass ratio of 2:4 to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer;

[0185] The parameters for unwinding in step (3) are as follows:

[0186] The unwinding tension is 0.5N / cm and the unwinding speed is 80m / min.

[0187] (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric;

[0188] The parameters of the hydroentanglement reinforcement in step (4) are as follows:

[0189] The number of hydroentanglement reinforcement passes is six;

[0190] For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle;

[0191] For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement;

[0192] As for the water needle pressure, the water needle pressure is controlled at 50 bar during the first hydroentanglement reinforcement, 120 bar during the second and third hydroentanglement reinforcement, 170 bar during the fourth hydroentanglement reinforcement, 120 bar during the fifth hydroentanglement reinforcement, and 90 bar during the sixth hydroentanglement reinforcement.

[0193] (5) The spunlace composite nonwoven fabric obtained in step (4) is immersed in a modifier, and then subjected to hot air penetration drying and shaping, and finally wound, slit and packaged.

[0194] In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:15;

[0195] The preparation method of the modifier is as follows:

[0196] The organic matter of formula I and the organic matter of formula II are stirred and mixed in a mass ratio of 1:1.5 to obtain a mixture, dimethyl sulfoxide (5 times the mass of the mixture) and dicyclohexylcarbodiimide (0.2 times the mass of the mixture) are added, and the mixture is heated at 60°C for 8 hours to obtain an organic matter of formula III, and then the organic matter of formula III is reacted by the following reaction: 1.1 times the mass of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is added to the organic matter of formula III, and stirred at room temperature for 30 minutes, 5 times the mass of the organic matter of formula III is added with a 28wt% ammonia solution, and stirred at room temperature for 2 hours, 3 times the mass of ether is added, and vacuum dried to obtain an off-white powder organic matter of formula IV;

[0197] The structure of Formula I is as follows:

[0198] (I),

[0199] The structure of Formula II is as follows:

[0200] (II), wherein the preparation method of the organic compound of formula II is as follows: 1 molar equivalent of guanidine thiourea is dissolved in 10 molar equivalents of 1 mol / L NaOH solution, cooled to 0°C in an ice bath, 1.1 molar equivalents of methyl cyanoacetate are slowly added dropwise, the temperature is controlled to be below 10°C, and the temperature is naturally raised to room temperature after the addition is completed, and the reaction is continued by stirring for 4 hours. After the reaction is completed, the pH is adjusted to 6 with dilute hydrochloric acid, and suction filtration is performed to obtain a white solid 2-amino-4-hydroxypyrimidine, then 1 molar equivalent of 2-amino-4-hydroxypyrimidine is dissolved in 10 molar equivalents of anhydrous methanol, 1.5 molar equivalents of anhydrous potassium carbonate are added, stirred, heated to reflux at 75°C, 1.2 molar equivalents of methyl iodide are slowly added dropwise, and the mixture is refluxed. The mixture was reacted for 4 hours, dissolved in dichloromethane, washed with water, and dried to obtain 2-amino-4-methoxypyrimidine. Then, 1 molar equivalent of 2-amino-4-methoxypyrimidine and 1.2 molar equivalents of ethyl acetoacetate were dissolved in 10 molar equivalents of anhydrous ethanol, heated under reflux at 80°C for 8 hours to obtain a pyrazolo[1,5-a]pyrimidine compound. 1 molar equivalent of the pyrazolo[1,5-a]pyrimidine skeleton compound was dissolved in 10 molar equivalents of N,N-dimethylformamide, cooled in an ice bath, and 1.2 molar equivalents of 60% by mass were slowly added. Sodium hydride, stirred for 20 minutes, slowly added 1.2 molar equivalents of N-(2-bromoethyl) anthranilic acid, naturally warmed to room temperature, continued to stir and react for 3 hours, dried to obtain an N-alkylated product, and finally, dissolved 1 molar equivalent of the N-alkylated product in 10 molar equivalents of anhydrous dichloromethane under ice bath cooling, slowly added 1.5 molar equivalents of chlorosulfonic acid, controlled the temperature below 5°C, naturally warmed to room temperature after the addition was completed, continued to stir and react for 4 hours, slowly poured the reaction solution into ice water, adjusted the pH to neutral, and dried to obtain;

[0201] The structure of Formula III is as follows:

[0202] (III),

[0203] The structure of Formula IV is as follows:

[0204] (IV).

[0205] The shaping method in step (5) is surface contact hot-ironing shaping, and its parameters are as follows:

[0206] The temperature is 160°C, the time is 3s, the pressure is 10N / mm, and the tension is 100N / m.

[0207] The modified composite nonwoven fabric material is prepared by the above-mentioned preparation process.

[0208] Implementation 2

[0209] The preparation process of the modified composite nonwoven fabric material comprises the following steps:

[0210] (1) The recycled polyester is melt-treated and spun to obtain a recycled polyester spunbond nonwoven fabric having a gram weight of 60 g / m 2 ;

[0211] The parameters of the recycled polyester in step (1) are as follows:

[0212] Melting point: 265°C, intrinsic viscosity: 0.65dl / g;

[0213] In step (1), the recycled polyester is subjected to the following treatment before being melt-treated:

[0214] The recycled polyester is melted at the melting point, and then crystallized, wherein the crystallization temperature is 150°C, and the crystallization time is 20 minutes. Finally, it is dried, wherein the drying temperature is 160°C, and the drying time is 8 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

[0215] The parameters of the melt treatment in step (1) are as follows:

[0216] A twin-screw extruder was used for melt extrusion, wherein the feed section temperature was 265°C, wherein the melting section temperature was 280°C, wherein the mixing section temperature was 280°C, wherein the discharge section temperature was 290°C;

[0217] The parameters of the spinning process in step (1) are as follows:

[0218] The temperature of the spinning box is controlled at 300° C., the air pressure of the airflow drafting device of the spinning box is controlled at 5 bar, the spinning speed of the spinning box is 1500 m / min, and the spinneret aperture of the spinning box is 0.2 mm.

[0219] (2) Opening and combing the recycled polyester staple fibers to obtain a recycled polyester staple fiber web with a density of 100 g / m 2 ;

[0220] The regenerated polyester staple fiber described in step (2) has a fineness of 1.7 dtex, a length of 38 mm, and contains 0.3% by mass of titanium dioxide matting agent.

[0221] The method of loosening in step (2) is as follows:

[0222] The feeding speed is 2m / min, the cylinder speed is 600rpm, the gap between the cylinder and the working roll is 1mm, and the air flow rate is 1m / s;

[0223] The method of combing in step (2) is as follows:

[0224] The card clothing density is 200 needles / inch, the production speed is 50m / min, and the draft ratio is 1.5 times.

[0225] (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) at a mass ratio of 5:1 to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer;

[0226] The parameters for unwinding in step (3) are as follows:

[0227] The unwinding tension is 2N / cm and the unwinding speed is 50m / min.

[0228] (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric;

[0229] The parameters of the hydroentanglement reinforcement in step (4) are as follows:

[0230] The number of hydroentanglement reinforcement passes is six;

[0231] For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle;

[0232] For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement;

[0233] As for the water needle pressure, the water needle pressure is controlled at 70 bar during the first hydroentanglement reinforcement, 100 bar during the second and third hydroentanglement reinforcement, 180 bar during the fourth hydroentanglement reinforcement, 100 bar during the fifth hydroentanglement reinforcement, and 110 bar during the sixth hydroentanglement reinforcement.

[0234] (5) The spunlace composite nonwoven fabric obtained in step (4) is immersed in a modifier, and then subjected to hot air penetration drying and shaping, and finally wound, slit and packaged.

[0235] In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:30;

[0236] The preparation method of the modifier is as follows:

[0237] The organic matter of formula I and the organic matter of formula II are stirred and mixed in a mass ratio of 1:2 to obtain a mixture, dimethyl sulfoxide (5 times the mass of the mixture) and dicyclohexylcarbodiimide (0.2 times the mass of the mixture) are added, and the mixture is heated at 60° C. for reaction for 8 hours to obtain an organic matter of formula III, and then the organic matter of formula III is reacted by the following reaction: 1.1 times the mass of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is added to the organic matter of formula III, and stirred at room temperature for 30 minutes, 5 times the mass of the organic matter of formula III is added with a 28wt% ammonia solution, and stirred at room temperature for 2 hours, 3 times the mass of ether is added, and vacuum drying is performed to obtain an off-white powder organic matter of formula IV;

[0238] The structure of Formula I is as follows:

[0239] (I),

[0240] The structure of Formula II is as follows:

[0241] (II), wherein the preparation method of the organic compound of formula II is as follows: 1 molar equivalent of guanidine thiourea is dissolved in 10 molar equivalents of 1 mol / L NaOH solution, cooled to 0°C in an ice bath, 1.1 molar equivalents of methyl cyanoacetate are slowly added dropwise, the temperature is controlled to be below 10°C, and the temperature is naturally raised to room temperature after the addition is completed, and the reaction is continued by stirring for 4 hours. After the reaction is completed, the pH is adjusted to 6 with dilute hydrochloric acid, and suction filtration is performed to obtain a white solid 2-amino-4-hydroxypyrimidine, then 1 molar equivalent of 2-amino-4-hydroxypyrimidine is dissolved in 10 molar equivalents of anhydrous methanol, 1.5 molar equivalents of anhydrous potassium carbonate are added, stirred, heated to reflux at 75°C, 1.2 molar equivalents of methyl iodide are slowly added dropwise, and the mixture is refluxed. The mixture was reacted for 4 hours, dissolved in dichloromethane, washed with water, and dried to obtain 2-amino-4-methoxypyrimidine. Then, 1 molar equivalent of 2-amino-4-methoxypyrimidine and 1.2 molar equivalents of ethyl acetoacetate were dissolved in 10 molar equivalents of anhydrous ethanol, heated under reflux at 80°C for 8 hours to obtain a pyrazolo[1,5-a]pyrimidine compound. 1 molar equivalent of the pyrazolo[1,5-a]pyrimidine skeleton compound was dissolved in 10 molar equivalents of N,N-dimethylformamide, cooled in an ice bath, and 1.2 molar equivalents of 60% by mass were slowly added. Sodium hydride, stirred for 20 minutes, slowly added 1.2 molar equivalents of N-(2-bromoethyl) anthranilic acid, naturally warmed to room temperature, continued to stir and react for 3 hours, dried to obtain an N-alkylated product, and finally, dissolved 1 molar equivalent of the N-alkylated product in 10 molar equivalents of anhydrous dichloromethane under ice bath cooling, slowly added 1.5 molar equivalents of chlorosulfonic acid, controlled the temperature below 5°C, naturally warmed to room temperature after the addition was completed, continued to stir and react for 4 hours, slowly poured the reaction solution into ice water, adjusted the pH to neutral, and dried to obtain;

[0242] The structure of Formula III is as follows:

[0243] (III),

[0244] The structure of Formula IV is as follows:

[0245] (IV).

[0246] The shaping method in step (5) is surface contact hot-ironing shaping, and its parameters are as follows:

[0247] The temperature is 220°C, the time is 1s, the pressure is 30N / mm, and the tension is 30N / m.

[0248] The modified composite nonwoven fabric material is prepared by the above-mentioned preparation process.

[0249] Implementation 3

[0250] The preparation process of the modified composite nonwoven fabric material comprises the following steps:

[0251] (1) The recycled polyester is melt-treated and spun to obtain a recycled polyester spunbond nonwoven fabric having a gram weight of 55 g / m 2 ;

[0252] The parameters of the recycled polyester in step (1) are as follows:

[0253] Melting point: 260°C, intrinsic viscosity: 0.70dl / g;

[0254] In step (1), the recycled polyester is subjected to the following treatment before being melt-treated:

[0255] The recycled polyester is melted at the melting point, and then crystallized, wherein the crystallization temperature is 145°C, and the crystallization time is 25 minutes. Finally, it is dried, wherein the drying temperature is 155°C, and the drying time is 9 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

[0256] The parameters of the melt treatment in step (1) are as follows:

[0257] A twin-screw extruder was used for melt extrusion, wherein the feed section temperature was 265°C, wherein the melting section temperature was 275°C, wherein the mixing section temperature was 283°C, wherein the discharge section temperature was 287°C;

[0258] The parameters of the spinning process in step (1) are as follows:

[0259] The temperature of the spinning manifold is controlled at 290° C., the air pressure of the airflow drafting device of the spinning manifold is controlled at 7 bar, the spinning speed of the spinning manifold is 1200 m / min, and the spinneret aperture of the spinning manifold is 0.3 mm.

[0260] (2) The regenerated polyester staple fibers are opened and combed to obtain a regenerated polyester staple fiber web having a density of 95 g / m 2 ;

[0261] The regenerated polyester staple fiber described in step (2) has a fineness of 1.5 dtex, a length of 45 mm, and contains 0.3% by mass of titanium dioxide matting agent.

[0262] The method of loosening in step (2) is as follows:

[0263] The feeding speed is 1m / min, the cylinder speed is 1200rpm, the gap between the cylinder and the working roll is 0.5mm, and the air flow rate is 5m / s;

[0264] The method of combing in step (2) is as follows:

[0265] The card clothing density is 160 needles / inch, the production speed is 70m / min, and the draft ratio is 1.3 times.

[0266] (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) in a mass ratio of 4:3 to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer;

[0267] The parameters for unwinding in step (3) are as follows:

[0268] The unwinding tension is 1N / cm and the unwinding speed is 70m / min.

[0269] (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric;

[0270] The parameters of the hydroentanglement reinforcement in step (4) are as follows:

[0271] The number of hydroentanglement reinforcement passes is six;

[0272] For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle;

[0273] For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement;

[0274] As for the water needle pressure, the water needle pressure is controlled at 60 bar during the first hydroentanglement reinforcement, 110 bar during the second and third hydroentanglement reinforcement, 175 bar during the fourth hydroentanglement reinforcement, 110 bar during the fifth hydroentanglement reinforcement, and 100 bar during the sixth hydroentanglement reinforcement.

[0275] (5) The spunlace composite nonwoven fabric obtained in step (4) is immersed in a modifier, and then subjected to hot air penetration drying and shaping, and finally wound, slit and packaged.

[0276] In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:22;

[0277] The preparation method of the modifier is as follows:

[0278] The organic matter of formula I and the organic matter of formula II are stirred and mixed in a mass ratio of 1:1.8 to obtain a mixture, dimethyl sulfoxide (7 times the mass of the mixture) and dicyclohexylcarbodiimide (0.2 times the mass of the mixture) are added, and the mixture is heated at 70°C for 6 hours to obtain an organic matter of formula III, followed by the following reaction: 1.3 times the mass of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is added to the organic matter of formula III, stirred at room temperature for 30 minutes, 4 times the mass of the organic matter of formula III is added with a 28wt% ammonia solution, stirred at room temperature for 3 hours, 2 times the mass of ether is added, and vacuum dried to obtain an off-white powder organic matter of formula IV;

[0279] The structure of Formula I is as follows:

[0280] (I),

[0281] The structure of Formula II is as follows:

[0282] (II), wherein the preparation method of the organic compound of formula II is as follows: 1 molar equivalent of guanidine thiourea is dissolved in 10 molar equivalents of 1 mol / L NaOH solution, cooled to 0°C in an ice bath, 1.1 molar equivalents of methyl cyanoacetate are slowly added dropwise, the temperature is controlled to be below 10°C, and the temperature is naturally raised to room temperature after the addition is completed, and the reaction is continued by stirring for 4 hours. After the reaction is completed, the pH is adjusted to 6 with dilute hydrochloric acid, and suction filtration is performed to obtain a white solid 2-amino-4-hydroxypyrimidine, then 1 molar equivalent of 2-amino-4-hydroxypyrimidine is dissolved in 10 molar equivalents of anhydrous methanol, 1.5 molar equivalents of anhydrous potassium carbonate are added, stirred, heated to reflux at 75°C, 1.2 molar equivalents of methyl iodide are slowly added dropwise, and the mixture is refluxed. The mixture was reacted for 4 hours, dissolved in dichloromethane, washed with water, and dried to obtain 2-amino-4-methoxypyrimidine. Then, 1 molar equivalent of 2-amino-4-methoxypyrimidine and 1.2 molar equivalents of ethyl acetoacetate were dissolved in 10 molar equivalents of anhydrous ethanol, heated under reflux at 80°C for 8 hours to obtain a pyrazolo[1,5-a]pyrimidine compound. 1 molar equivalent of the pyrazolo[1,5-a]pyrimidine skeleton compound was dissolved in 10 molar equivalents of N,N-dimethylformamide, cooled in an ice bath, and 1.2 molar equivalents of 60% by mass were slowly added. Sodium hydride, stirred for 20 minutes, slowly added 1.2 molar equivalents of N-(2-bromoethyl) anthranilic acid, naturally warmed to room temperature, continued to stir and react for 3 hours, dried to obtain an N-alkylated product, and finally, dissolved 1 molar equivalent of the N-alkylated product in 10 molar equivalents of anhydrous dichloromethane under ice bath cooling, slowly added 1.5 molar equivalents of chlorosulfonic acid, controlled the temperature below 5°C, naturally warmed to room temperature after the addition was completed, continued to stir and react for 4 hours, slowly poured the reaction solution into ice water, adjusted the pH to neutral, and dried to obtain;

[0283] The structure of Formula III is as follows:

[0284] (III),

[0285] The structure of Formula IV is as follows:

[0286] (IV).

[0287] The shaping method in step (5) is surface contact hot-ironing shaping, and its parameters are as follows:

[0288] The temperature is 200°C, the time is 2s, the pressure is 20N / mm, and the tension is 70N / m.

[0289] The modified composite nonwoven fabric material prepared by the above-mentioned preparation process, such as Figure 1 As shown, it demonstrates the microscopic effects of the prepared material.

[0290] in Figure 2 and Figure 3The hydrogen spectrum and carbon spectrum of the modifier are shown. Specifically, the hydrogen spectrum data: 1H NMR: δ7.81 (2H), 7.64 (2H), 5.53 (4H), 5.37 (2H), 4.37 (1H), 4.26 (1H), 4.00 (3H), 2.83 (4H), 2.33 (2H), 1.92 (2H), carbon spectrum data: 13C NMR: δ 173.82 (1C), 173.56 (1C), 168.60 (1C), 167.57 (1C), 157.82 (1C), 154.58 (1C), 150.19 (1C), 148.14 (1C), 128.02 (2C), 122.70 (1C), 112.50 (2C), 99.90 (1C), 57.63 (1C), 52.36 (1C), 47.05 (2C), 30.09 (1C), 26.10 (1C).

[0291] In addition, for other substances in the synthesis process of the modifier, the organic compound of formula I, hydrogen spectrum data: 1H NMR: δ 5.37 (2H), 4.00 (2H), 3.78 (1H), 2.33 (2H), 1.78 (2H), carbon spectrum data: 13C NMR: δ 175.38 (1C), 173.82 (1C), 55.86 (1C), 34.64 (1C), 28.16 (1C). The organic compound of formula II, such as Figure 4 and Figure 5 As shown, hydrogen spectrum data: 1H NMR: δ 11.20 (1H), 8.00 (2H), 7.64 (2H), 6.09 (1H), 5.53 (3H), 4.37 (1H), 4.00 (3H), 3.33 (3H), 2.83 (4H), carbon spectrum data: 13C NMR: δ 168.60 (1C), 167.10 (1C), 154.66 (1C), 150.19 (1C), 148.14 (1C), 136.30 (1C), 130.43 (2C), 125.95 (1C), 111.72 (2C), 87.22 (1C), 57.63 (1C), 55.40 (1C), 47.05 (2C). The organic compound of formula III, such as Figure 6 and Figure 7As shown, hydrogen spectrum data: 1H NMR: δ 7.81 (2H), 7.64 (2H), 6.09 (1H), 5.53 (4H), 5.37 (2H), 4.37 (1H), 4.26 (1H), 4.00 (3H), 3.33 (3H), 2.83 (4H), 2.33 (2H), 1.90 (2H), carbon spectrum data: 13C NMR: δ 173.82 (1C), 173.56 (1C), 168.60 (1C), 167.57 (1C), 154.66 (1C), 150.19 (1C), 148.14 (1C), 136.30 (1C), 128.02 (2C), 122.70 (1C), 112.50 (2C), 87.22 (1C), 57.63(1C), 55.40 (1C), 52.36 (1C), 47.05 (2C), 30.09 (1C), 26.10 (1C).

[0292] Comparison plan 1

[0293] The preparation process of the modified composite nonwoven fabric material comprises the following steps:

[0294] (1) The recycled polyester is melt-treated and spun to obtain a recycled polyester spunbond nonwoven fabric having a gram weight of 55 g / m 2 ;

[0295] The parameters of the recycled polyester in step (1) are as follows:

[0296] Melting point: 260°C, intrinsic viscosity: 0.70dl / g;

[0297] In step (1), the recycled polyester is subjected to the following treatment before being melt-treated:

[0298] The recycled polyester is melted at the melting point, and then crystallized, wherein the crystallization temperature is 145°C, and the crystallization time is 25 minutes. Finally, it is dried, wherein the drying temperature is 155°C, and the drying time is 9 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

[0299] The parameters of the melt treatment in step (1) are as follows:

[0300] A twin-screw extruder was used for melt extrusion, wherein the feed section temperature was 265°C, wherein the melting section temperature was 275°C, wherein the mixing section temperature was 283°C, wherein the discharge section temperature was 287°C;

[0301] The parameters of the spinning process in step (1) are as follows:

[0302] The temperature of the spinning manifold is controlled at 290° C., the air pressure of the airflow drafting device of the spinning manifold is controlled at 7 bar, the spinning speed of the spinning manifold is 1200 m / min, and the spinneret aperture of the spinning manifold is 0.3 mm.

[0303] (2) The regenerated polyester staple fibers are opened and combed to obtain a regenerated polyester staple fiber web having a density of 95 g / m 2 ;

[0304] The regenerated polyester staple fiber described in step (2) has a fineness of 1.5 dtex, a length of 45 mm, and contains 0.3% by mass of titanium dioxide matting agent.

[0305] The method of loosening in step (2) is as follows:

[0306] The feeding speed is 1m / min, the cylinder speed is 1200rpm, the gap between the cylinder and the working roll is 0.5mm, and the air flow rate is 5m / s;

[0307] The method of combing in step (2) is as follows:

[0308] The card clothing density is 160 needles / inch, the production speed is 70m / min, and the draft ratio is 1.3 times.

[0309] (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) in a mass ratio of 4:3 to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer;

[0310] The parameters for unwinding in step (3) are as follows:

[0311] The unwinding tension is 1N / cm and the unwinding speed is 70m / min.

[0312] (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric;

[0313] The parameters of the hydroentanglement reinforcement in step (4) are as follows:

[0314] The number of hydroentanglement reinforcement passes is six;

[0315] For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle;

[0316] For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement;

[0317] As for the water needle pressure, the water needle pressure is controlled at 60 bar during the first hydroentanglement reinforcement, 110 bar during the second and third hydroentanglement reinforcement, 175 bar during the fourth hydroentanglement reinforcement, 110 bar during the fifth hydroentanglement reinforcement, and 100 bar during the sixth hydroentanglement reinforcement.

[0318] (5) The spunlace composite nonwoven fabric obtained in step (4) is immersed in a modifier, and then subjected to hot air penetration drying and shaping, and finally wound, slit and packaged.

[0319] In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:22;

[0320] The modifier is toluene diisocyanate.

[0321] The shaping method in step (5) is surface contact hot-ironing shaping, and its parameters are as follows:

[0322] The temperature is 200°C, the time is 2s, the pressure is 20N / mm, and the tension is 70N / m.

[0323] The modified composite nonwoven fabric material is prepared by the above-mentioned preparation process.

[0324] Comparison plan 2

[0325] The preparation process of the modified composite nonwoven fabric material comprises the following steps:

[0326] (1) The recycled polyester is melt-treated and spun to obtain a recycled polyester spunbond nonwoven fabric having a gram weight of 55 g / m 2 ;

[0327] The parameters of the recycled polyester in step (1) are as follows:

[0328] Melting point: 260°C, intrinsic viscosity: 0.70dl / g;

[0329] In step (1), the recycled polyester is subjected to the following treatment before being melt-treated:

[0330] The recycled polyester is melted at the melting point, and then crystallized, wherein the crystallization temperature is 145°C, and the crystallization time is 25 minutes. Finally, it is dried, wherein the drying temperature is 155°C, and the drying time is 9 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

[0331] The parameters of the melt treatment in step (1) are as follows:

[0332] A twin-screw extruder was used for melt extrusion, wherein the feed section temperature was 265°C, wherein the melting section temperature was 275°C, wherein the mixing section temperature was 283°C, wherein the discharge section temperature was 287°C;

[0333] The parameters of the spinning process in step (1) are as follows:

[0334] The temperature of the spinning manifold is controlled at 290° C., the air pressure of the airflow drafting device of the spinning manifold is controlled at 7 bar, the spinning speed of the spinning manifold is 1200 m / min, and the spinneret aperture of the spinning manifold is 0.3 mm.

[0335] (2) The regenerated polyester staple fibers are opened and combed to obtain a regenerated polyester staple fiber web having a density of 95 g / m 2 ;

[0336] The regenerated polyester staple fiber described in step (2) has a fineness of 1.5 dtex, a length of 45 mm, and contains 0.3% by mass of titanium dioxide matting agent.

[0337] The method of loosening in step (2) is as follows:

[0338] The feeding speed is 1m / min, the cylinder speed is 1200rpm, the gap between the cylinder and the working roll is 0.5mm, and the air flow rate is 5m / s;

[0339] The method of combing in step (2) is as follows:

[0340] The card clothing density is 160 needles / inch, the production speed is 70m / min, and the draft ratio is 1.3 times.

[0341] (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) in a mass ratio of 4:3 to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer;

[0342] The parameters for unwinding in step (3) are as follows:

[0343] The unwinding tension is 1N / cm and the unwinding speed is 70m / min.

[0344] (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric;

[0345] The parameters of the hydroentanglement reinforcement in step (4) are as follows:

[0346] The number of hydroentanglement reinforcement passes is six;

[0347] For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle;

[0348] For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement;

[0349] As for the water needle pressure, the water needle pressure is controlled at 60 bar during the first hydroentanglement reinforcement, 110 bar during the second and third hydroentanglement reinforcement, 175 bar during the fourth hydroentanglement reinforcement, 110 bar during the fifth hydroentanglement reinforcement, and 100 bar during the sixth hydroentanglement reinforcement.

[0350] (5) The spunlace composite nonwoven fabric obtained in step (4) is immersed in a modifier, and then subjected to hot air penetration drying and shaping, and finally wound, slit and packaged.

[0351] In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:22;

[0352] The modifier is an organic compound of formula II, wherein the structure of formula II is as follows:

[0353] (II), wherein the preparation method of the organic compound of formula II is as follows: 1 molar equivalent of guanidine thiourea is dissolved in 10 molar equivalents of 1 mol / L NaOH solution, cooled to 0°C in an ice bath, 1.1 molar equivalents of methyl cyanoacetate are slowly added dropwise, the temperature is controlled to be below 10°C, and the temperature is naturally raised to room temperature after the addition is completed, and the reaction is continued by stirring for 4 hours. After the reaction is completed, the pH is adjusted to 6 with dilute hydrochloric acid, and suction filtration is performed to obtain a white solid 2-amino-4-hydroxypyrimidine, then 1 molar equivalent of 2-amino-4-hydroxypyrimidine is dissolved in 10 molar equivalents of anhydrous methanol, 1.5 molar equivalents of anhydrous potassium carbonate are added, stirred, heated to reflux at 75°C, 1.2 molar equivalents of methyl iodide are slowly added dropwise, and the mixture is refluxed. The mixture was reacted for 4 hours, dissolved in dichloromethane, washed with water, and dried to obtain 2-amino-4-methoxypyrimidine. Then, 1 molar equivalent of 2-amino-4-methoxypyrimidine and 1.2 molar equivalents of ethyl acetoacetate were dissolved in 10 molar equivalents of anhydrous ethanol, heated under reflux at 80°C for 8 hours to obtain a pyrazolo[1,5-a]pyrimidine compound. 1 molar equivalent of the pyrazolo[1,5-a]pyrimidine skeleton compound was dissolved in 10 molar equivalents of N,N-dimethylformamide, cooled in an ice bath, and 1.2 molar equivalents of 60% by mass were slowly added. Sodium hydride, stir for 20 minutes, slowly drop 1.2 molar equivalents of N-(2-bromoethyl) anthranilic acid, naturally warm to room temperature, continue to stir and react for 3 hours, dry to obtain N-alkylated product, finally, dissolve 1 molar equivalent of N-alkylated product in 10 molar equivalents of anhydrous dichloromethane under ice bath cooling, slowly drop 1.5 molar equivalents of chlorosulfonic acid, control the temperature below 5°C, naturally warm to room temperature after the addition is completed, continue to stir and react for 4 hours, slowly pour the reaction solution into ice water, adjust the pH to neutral, and dry to obtain.

[0354] The shaping method in step (5) is surface contact hot-ironing shaping, and its parameters are as follows:

[0355] The temperature is 200°C, the time is 2s, the pressure is 20N / mm, and the tension is 70N / m.

[0356] The modified composite nonwoven fabric material is prepared by the above-mentioned preparation process.

[0357] Test plan:

[0358] Softness test

[0359] Referring to ISO 9073-9 "Textiles - Test methods for nonwovens - Part 9: Determination of drape and drape coefficient", the drape method is used to test the softness of nonwovens.

[0360] Measurement range: Softness index, usually ranging from 0-100, with higher values ​​indicating softer fabrics.

[0361] The specific test method is as follows:

[0362] Prepare multiple nonwoven fabric samples of the same size, the standard size is usually 100mm x 100mm.

[0363] The nonwoven fabric sample is suspended horizontally on the testing equipment.

[0364] Allow the sample to hang freely and measure its hanging height (h) under the action of gravity.

[0365] Record the overhang angle (θ), which can be found by observing the displacement of the sample from the nominal position.

[0366] Repeat the above steps at least three times to obtain the average value and ensure the stability of the data.

[0367] According to ISO standards, the softness index can be calculated by the following formula:

[0368] Softness index = h / cos (θ) × 100.

[0369] Hygroscopicity test

[0370] The hygroscopicity of nonwoven fabrics was tested according to ISO 9073-18 “Textiles - Test methods for nonwovens - Part 18: Determination of hygroscopicity”.

[0371] Measuring range: Hygroscopicity index, usually ranging from 0-100, the higher the value, the easier it is to absorb moisture.

[0372] The specific test method is as follows:

[0373] Select a nonwoven fabric sample of appropriate size, usually 100mm x 100mm.

[0374] Use a precise balance (with an accuracy of at least 0.001 g) to measure the mass of the sample.

[0375] Initial mass measurement: Place the dry sample on a balance and record its initial mass M0.

[0376] Place the sample in a constant humidity chamber and maintain it at a set humidity (e.g. 75%) and temperature (e.g. 23°C) to reach equilibrium. It is recommended to place it in the humidity chamber for 24 hours to ensure that the sample fully absorbs moisture.

[0377] Take the sample out of the humidity chamber and quickly measure its mass M1.

[0378] Record the mass after moisture absorption for subsequent calculations.

[0379] Calculate the hygroscopicity index of the sample using the following formula:

[0380] Hygroscopicity index = (M1-M0) / M0×100.

[0381] Corrosion resistance test

[0382] Refer to ISO 12945-1 "Textiles - Test for resistance to chemical substances - Part 1: Test for attack by chemical substances under specified conditions" to test the corrosion resistance of nonwoven fabrics.

[0383] Measuring range: Corrosion resistance index, usually ranging from 0-100, the higher the value, the more corrosion resistant it is.

[0384] The specific test method is as follows:

[0385] Select a nonwoven fabric sample of appropriate size, usually 100mm x 100mm.

[0386] Select the corrosive medium:

[0387] Determine the type of corrosive medium to be tested, such as a dilute hydrochloric acid solution with a mass concentration of 5%.

[0388] Immersion experiment:

[0389] The samples were placed in the corrosive medium and the exposure time was recorded for 72 h.

[0390] After soaking, remove the samples and quickly rinse with water.

[0391] After the samples were dried, the mass of the samples was measured.

[0392] Before and after immersion in the corrosive medium, record the initial mass M0 and the mass after immersion M1.

[0393] The corrosion resistance index of the samples was calculated using the following formula:

[0394] Corrosion resistance index = (M1-M0) / M0×100.

[0395] Table 1 Test results

[0396]

[0397] It can be seen from the data that the softness of implementation schemes 1-3 is above 93, which is significantly higher than 80-85 of comparison scheme 1-2. The hygroscopicity of implementation schemes 1-3 is above 95, which is significantly higher than 75-80 of comparison scheme 1-2. The corrosion resistance of implementation schemes 1-3 is above 95, which is significantly higher than 70-75 of comparison scheme 1-2. Therefore, the implementation scheme of the present invention is significantly better than the comparison scheme in terms of softness, hygroscopicity and corrosion resistance. Comparative scheme 1 only uses toluene diisocyanate as a modifier. Toluene diisocyanate (TDI) is a commonly used isocyanate compound. It contains two highly active -NCO groups. When TDI is used as a modifier in contact with the spunlace composite non-woven fabric, the -NCO group in the TDI molecule will react chemically with the active hydrogen (such as hydroxyl -OH, amino -NH2, etc.) on the surface of the non-woven fabric to form a carbamate (-NHCOO-) bond. This chemical bonding causes the TDI molecule to be "grafted" onto the surface of the non-woven fabric, changing the surface properties of the non-woven fabric. TDI grafting modification can improve the hydrophobicity of the non-woven surface because TDI molecules contain hydrophobic toluene rings. In addition, TDI molecules also undergo self-crosslinking to form a hydrophobic polymer coating on the surface of the non-woven fabric. This further enhances the hydrophobic and waterproof effects of the non-woven fabric. However, there are some problems with modification using only TDI: TDI's high toxicity and volatility pose health risks. Residual free TDI monomers can irritate the skin and respiratory tract. TDI is easily hydrolyzed at room temperature to produce toxic aromatic amines. This reduces the durability of the modification effect. TDI molecules are relatively rigid, and the softness and air permeability of the modified non-woven fabric decrease. Single TDI modification provides limited performance improvement and is difficult to meet practical application requirements.

[0398] Comparative Scheme 2 selects organic matter of Formula II as the modifier, which contains the following active groups; Sulfonic acid group (-SO3H): It is a strong polar group that can be adsorbed on the surface of non-woven fabrics through electrostatic action, thereby improving the hydrophilicity and hygroscopicity of the material. Carboxyl group (-COOH): It is also a polar group that can form hydrogen bonds with the hydroxyl groups in the cellulose molecules to enhance the bonding between the modifier and the fiber. Secondary amine group (-NH-): It can be used as a proton receptor to form hydrogen bonds, further enhancing the intermolecular forces. At the same time, the secondary amine group can also react chemically with the epoxy group on the cellulose. Pyrimidine ring and pyrazole ring: These nitrogen-containing heterocyclic rings can be combined with the fiber surface through forces such as π-π stacking, thereby increasing the adsorption amount of the modifier. Methoxy group (-OCH3): It can slightly increase the hydrophobicity of the molecule, which helps to maintain adsorption during the hydroentanglement process. The introduction of sulfonic acid group, carboxyl group, and secondary amine group in the molecule of Formula II significantly improves its affinity with the fiber, allowing it to be firmly adsorbed on the surface of the non-woven fabric. On the one hand, the adsorbed modifier can enhance the hydrophilicity of the material surface and increase the moisture absorption rate; on the other hand, the presence of polar groups also gives the material certain antistatic properties. However, the relative molecular weight of the formula II molecule is large, and the steric hindrance effect is obvious, making it difficult to penetrate into the fiber. Moreover, the molecule lacks active reactive groups such as epoxy groups, and mainly relies on physical forces to bind, so the durability of the modification effect is poor and the anti-washing performance is poor. In summary, the organic matter of formula II is used as a modifier, and its polar groups can significantly improve the hydrophilicity and hygroscopicity of the material, but lacks the ability to chemically bond with the fiber, so the modification effect is not durable enough, which is the reason why its performance indicators are lower than those of the embodiment of the present invention.

[0399] In addition, as shown in Table 2 below, taking the modified composite nonwoven fabric material prepared in Implementation Example 3 as an example, "RJSS100A95" is the internal code of the product, that is, Ruiju spunbond nonwoven fabric spunlace composite plain weave 95g / m 2 The physical indicators of the product, 5 different samples (i.e., items 1-5) of the same batch are listed, including gram weight, thickness, breaking strength, breaking elongation and width. The test of gram weight refers to the national standard GB / T 24218.1-2009 "Test methods for textile nonwovens Part 1: Determination of mass per unit area"; the test of thickness refers to the national standard GB / T 24218.2-2009 "Test methods for textile nonwovens Part 2: Determination of thickness"; the test of breaking strength and breaking elongation refers to the national standard GB / T24218.3-2010 "Test methods for textile nonwovens Part 3: Determination of breaking strength and breaking elongation (strip method)"; the test method of width (i.e., width) has no corresponding national standard, and it is carried out in the following way, using simple measuring tools (such as tape measures, etc.). During the test, the sample should be ensured to be in a flat and non-stretched state, and the measurement should be carried out along the width direction of the sample.

[0400] It should be noted that in Table 2, "T spunbond 60% / T40%", T spunbond: "T" here usually refers to polyester (PET). Spunbond is a non-woven fabric material made by spinning and bonding processes, with good strength and durability. 60% / 40%: This represents the proportion of the two components in the composite material. Here, T spunbond accounts for 60% of the entire material, and the other component is 40%. T40%: The other component here is also polyester (PET), but it refers to a recycled polyester staple fiber web. The staple fibers are formed into a fiber web through processes such as opening and carding, and after being compounded with spunbond, the material is given softness and better moisture absorption. In summary, T spunbond 60% / T40% means that the non-woven fabric material is composed of 60% recycled polyester spunbond non-woven fabric and 40% recycled polyester staple fiber web. According to the text in step (3) of implementation scheme 3: "The recycled polyester spunbond nonwoven fabric obtained in step (1) is unwound, and then laminated with the recycled polyester staple fiber web obtained in step (2) in a mass ratio of 4:3 to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven is arranged in a relatively lower layer, and the recycled polyester staple fiber web is placed in a relatively upper layer", the "4:3" mass ratio here clearly indicates that the ratio of the recycled polyester spunbond nonwoven fabric to the recycled polyester staple fiber web is 4 parts to 3 parts. Add 4 parts to 3 parts, a total of 7 parts, 4 parts account for 60% of the total parts, and 3 parts account for 40% of the total parts. Therefore, it can be determined that the modified composite nonwoven fabric material is composited by 60% of the recycled polyester spunbond nonwoven fabric and 40% of the recycled polyester staple fiber web in a mass ratio.

[0401] It should be noted that the "average value X" in Table 2 is the average value obtained by summing up all the test values ​​of the 5 samples under each test item. MD (Machine Direction): refers to the tensile strength or performance of the material along the machine running direction during the production process, also known as the longitudinal direction. CD (Cross Direction): refers to the tensile strength or performance perpendicular to the machine running direction, also known as the transverse direction.

[0402] These data are crucial for evaluating the performance of spunlace nonwovens. By calculating the average value of each indicator, we can get a clearer understanding of the overall performance: Average gram weight: 94.00 g / m², which indicates that the sample as a whole is a medium-weight nonwoven. Average thickness: 0.57 mm, showing good thickness control. Average breaking strength: MD direction: 256.00N / 50mm, CD direction: 161.48 N / 50mm; This shows that the strength of the material in the machine direction is significantly higher than that in the vertical direction, which is in line with the common characteristics of textiles. Average elongation at break: MD direction: 24.49%, CD direction: 20.68%, indicating that the material has a certain elasticity and is suitable for a variety of application scenarios. Combined with the above data, the spunlace nonwoven of Implementation Plan 3 can be evaluated as follows: Comprehensive performance: The nonwoven fabric shows a good balance in gram weight, thickness and strength, and is suitable for applications that require a certain strength and flexibility, such as medical and health, personal care and other fields. Applicability: Due to its good elongation at break, the material can adapt to a certain degree of deformation, which increases its scope of application in practical applications. Modification effect: The modifier used in Implementation Plan 3 and its preparation process may have played a positive role in improving the performance of the material, which can be further verified through subsequent experiments. The data of Implementation Plan 3 show that the spunlace nonwoven fabric exhibits good performance in multiple physical indicators. By conducting in-depth analysis of these data, it can provide important reference for subsequent product development and market application. In the actual production process, maintaining the consistency of these indicators will be the key to ensuring product quality and meeting market demand.

[0403] Table 2 Physical index test

[0404]

[0405] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A process for preparing a modified composite nonwoven fabric material, comprising the following steps: (1) The recycled polyester chips are melt-treated and spun to obtain recycled polyester spunbond nonwoven fabric with a gram weight of 50-60 g / m 2 ; (2) opening and combing the regenerated polyester staple fibers to obtain a regenerated polyester staple fiber web; (3) unwinding the recycled polyester spunbond nonwoven fabric obtained in step (1), and laminating the recycled polyester staple fiber web obtained in step (2) in a mass ratio of (2-5):(1-4) to obtain a laminated composite material, wherein the recycled polyester spunbond nonwoven fabric is arranged on a relatively lower layer, and the recycled polyester staple fiber web is arranged on a relatively upper layer; (4) hydroentangling and reinforcing the laminated composite material obtained in step (3) to obtain a hydroentangled composite nonwoven fabric; (5) The spunlace composite nonwoven fabric obtained in step (4) is immersed in a modifier for modification, and then washed and dehydrated, and then hot air is penetrated to dry and shape it, and finally it is wound, slit and packaged; In step (5), the mass ratio between the spunlace composite nonwoven fabric and the modifier is 1:(15-30); The preparation method of the modifier is as follows: An organic substance of formula I and an organic substance of formula II are stirred and mixed in a mass ratio of 1:(1.5-2) to obtain a mixture, dimethyl sulfoxide (5-8 times the mass of the mixture) and dicyclohexylcarbodiimide (0.1-0.2 times the mass of the mixture) are added, and the mixture is heated at 60-75° C. for reaction for 4-8 hours to obtain an organic substance of formula III, and then the organic substance of formula III is reacted by the following reaction: 1.1-1.5 times the mass of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is added to the organic substance of formula III, and stirred at room temperature for 30 minutes, 28wt% ammonia solution (3-5 times the mass of the organic substance of formula III) is added, and stirred at room temperature for 2-4 hours, 2-3 times the mass of ether is added, and vacuum drying is performed to obtain a white or off-white powder organic substance of formula IV; The structure of Formula I is as follows: (I), The structure of Formula II is as follows: (II), wherein the preparation method of the organic compound of formula II is as follows: 1 molar equivalent of guanidine thiourea is dissolved in 10 molar equivalents of 1 mol / L NaOH solution, cooled to 0°C in an ice bath, 1.1 molar equivalents of methyl cyanoacetate are slowly added dropwise, the temperature is controlled to be below 10°C, and the temperature is naturally raised to room temperature after the addition is completed, and the reaction is continued by stirring for 4 hours. After the reaction is completed, the pH is adjusted to 6 with dilute hydrochloric acid, and suction filtration is performed to obtain a white solid 2-amino-4-hydroxypyrimidine, then 1 molar equivalent of 2-amino-4-hydroxypyrimidine is dissolved in 10 molar equivalents of anhydrous methanol, 1.5 molar equivalents of anhydrous potassium carbonate are added, stirred, heated to reflux at 75°C, 1.2 molar equivalents of methyl iodide are slowly added dropwise, and the mixture is refluxed. The mixture was reacted for 4 hours, dissolved in dichloromethane, washed with water, and dried to obtain 2-amino-4-methoxypyrimidine. Then, 1 molar equivalent of 2-amino-4-methoxypyrimidine and 1.2 molar equivalents of ethyl acetoacetate were dissolved in 10 molar equivalents of anhydrous ethanol, heated under reflux at 80°C for 8 hours to obtain a pyrazolo[1,5-a]pyrimidine compound. 1 molar equivalent of the pyrazolo[1,5-a]pyrimidine skeleton compound was dissolved in 10 molar equivalents of N,N-dimethylformamide, cooled in an ice bath, and 1.2 molar equivalents of 60% by mass were slowly added. Sodium hydride, stirred for 20 minutes, slowly added 1.2 molar equivalents of N-(2-bromoethyl) anthranilic acid, naturally warmed to room temperature, continued to stir and react for 3 hours, dried to obtain an N-alkylated product, and finally, dissolved 1 molar equivalent of the N-alkylated product in 10 molar equivalents of anhydrous dichloromethane under ice bath cooling, slowly added 1.5 molar equivalents of chlorosulfonic acid, controlled the temperature below 5°C, naturally warmed to room temperature after the addition was completed, continued to stir and react for 4 hours, slowly poured the reaction solution into ice water, adjusted the pH to neutral, and dried to obtain; The structure of Formula III is as follows: (III), The structure of Formula IV is as follows: (IV)。 2. The preparation process of the modified composite nonwoven fabric material according to claim 1, characterized in that: The parameters of the recycled polyester in step (1) are as follows: Melting point: (250-265) ± 2°C, intrinsic viscosity: (0.65-0.75) ± 0.025 dl / g; In step (1), the recycled polyester is subjected to the following treatment before being melt-treated: The recycled polyester chips are dried and crystallized, wherein the crystallization temperature is 140-150°C, and the crystallization time is 20-30 minutes. Finally, they are dried, wherein the drying temperature is 150-160°C, and the drying time is 8-10 hours. After drying, the moisture content of the recycled polyester does not exceed 20ppm.

3. The preparation process of the modified composite nonwoven fabric material according to claim 1, characterized in that: The parameters of the melt treatment in step (1) are as follows: A twin-screw extruder is used for melt extrusion, wherein the feed section temperature is 265°C, wherein the melting section temperature is 270-280°C, wherein the mixing section temperature is 280-285°C, wherein the discharge section temperature is 285-290°C; The parameters of the spinning process in step (1) are as follows: The temperature of the spinning box is controlled at 280-300°C, the air pressure of the airflow drafting device of the spinning box is controlled at 5-8 bar, the spinning speed of the spinning box is 800-1500 m / min, and the spinneret aperture of the spinning box is 0.2-0.4 mm.

4. The preparation process of the modified composite nonwoven fabric material according to claim 1, characterized in that: The regenerated polyester staple fiber described in step (2) has a fineness of 1.3-1.7 dtex, a length of 38-51 mm, and contains a titanium dioxide matting agent in an amount of (0.3±0.02)% by mass.

5. The preparation process of the modified composite nonwoven fabric material according to claim 1, characterized in that: The method of loosening in step (2) is as follows: The feeding speed is 0.5-2m / min, the cylinder speed is 600-1500rpm, the gap between the cylinder and the working roll is 0.1-1mm, and the air flow rate is 1-10m / s; The method of combing in step (2) is as follows: The density of the card clothing is 120-200 needles / inch, the production speed is 50-80m / min, and the drafting multiple is 1.2-1.5 times.

6. The process for preparing the modified composite nonwoven fabric material according to claim 1, characterized in that: The parameters for unwinding in step (3) are as follows: The unwinding tension is 0.5-2N / cm and the unwinding speed is 50-80m / min.

7. The process for preparing the modified composite nonwoven fabric material according to claim 1, characterized in that: The parameters of the hydroentanglement reinforcement in step (4) are as follows: The number of hydroentanglement reinforcement passes is six; For the case where the water needle is facing, when the first, second, third, fifth, and sixth water entanglement reinforcements are made, the recycled polyester staple fiber web faces the water needle, and when the fourth water entanglement reinforcement is made, the recycled polyester spunbond nonwoven fabric faces the water needle; For the water needle aperture, the water needle aperture is set to 0.14mm for the first water entanglement reinforcement, and the water needle aperture is set to 0.1mm for the second to sixth water entanglement reinforcement; As for the water needle pressure, the water needle pressure is controlled at 50-70bar during the first hydroentanglement reinforcement, 100-120bar during the second and third hydroentanglement reinforcement, 170-180bar during the fourth hydroentanglement reinforcement, 100-120bar during the fifth hydroentanglement reinforcement, and 90-110bar during the sixth hydroentanglement reinforcement.

8. The process for preparing the modified composite nonwoven fabric material according to claim 1, characterized in that: The shaping method in step (5) is surface contact hot-ironing shaping, and its parameters are as follows: The temperature is 160-220℃, the time is 1-3s, the pressure is 10-30N / mm, and the tension is 30-100N / m.

9. A modified composite nonwoven fabric material, characterized in that: The modified composite nonwoven fabric material is prepared by the preparation process of the modified composite nonwoven fabric material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Nonwoven material for acoustic insulation, and process for manufacture

    CN102963107A

  • Light and thin composite non-woven fabric high in performance and producing method thereof

    CN104963101A